Catching-up development of the followers - Chi, Hoang Lan; Minh, Hoang Binh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Developing to catch up with leading countries is always the desire of the followers. These are also phenomena that have occurred at different periods in history. The characteristic of catching-up development is to make a difference in the way implement its development as to eliminate the gap in the level of development or the position in development pathway. Although the capacity in scientific research and technological development is still modest, the followers can improve their national science and technology (S&T) capacities through enhancing of applicability of S&T in production. The follow-up countries can exploit the differences between capabilities that are suitable for current context and those that are suitable for future requirements. Technical and S&T related economic development often changes over time. A good preparation of these abilities for catching-up development will enable the followers to rise up and catch up their ahead leading ones. Code: 17031401